Identification of seven undescribed cucurbitacins in Cucumis sativus (cucumber) and their cytotoxic activity. (May 2022) - Qing, Zhixing; Shi, Yao; Han, Lida; Li, Pengkun; Zha, Ziou; Liu, Chang; Liu, Xiubin; Huang, Peng; Liu, Yisong; Tang, Qi; Zeng, Kewu; Zeng, Jianguo; et al.
Abstract: Cucurbitacin C-type cucurbitacins that are only identified in Cucumis sativus (cucumber) are, in part, responsible for the health benefits and bitter flavor. Nevertheless, detailed information about those functional ingredients in cucumber is scarce. In this study, ten cucurbitacin C analogues including seven undescribed ones have been isolated from the bitter leaves of cucumber, in which six compounds showed growth inhibition capabilities against tumor cell lines HepG2, A549, DU145 and HCT116. Intriguingly, cucurbitacin C6 and C7 exhibited a significant inhibition effect compared to the positive control taxol (IC50  = 1.86 ± 0.17 μM) on HepG2 cell line with IC50 values of 10.06 ± 0.34 μM and 4.16 ± 0.42 μM, respectively. The mechanism of cucurbitacin-induced apoptosis is likely down-regulating the expression of caspase-related proteins. This work enlarges the knowledge of the cucurbitacins in cucumber and highlights the importance of cucumber as a source of specialized metabolites in the food and medicinal industries. Graphical abstract: Image 1 Highlights: Ten cucurbitacin C analogues including 7 undescribed ones were isolated in C. sativus . Two triterpenoids display similar cytotoxic activity to taxol on the tumor cell line. The C-25-acetyl group and α, β-unsaturated ketone were keys for their cytotoxicity. The mechanism is likely down-regulating the expression of caspase-related proteins.